Work Function Engineering of Thin α‐RuCl3 by Argon Sputtering. Issue 29 (7th September 2022) - Klaproth, Tom; Grönke, Martin; Hampel, Silke; Knupfer, Martin; Büchner, Bernd; Isaeva, Anna; Doert, Thomas; Koitzsch, Andreas
Abstract: α‐RuCl3 is a candidate material for the realization of a Kitaev spin liquid with envisioned applications for quantum computing. It is a van‐der‐Waals material with in‐plane honeycomb lattice equivalent to the Cr X 3 ( X = Cl, Br, I) type 2D magnets. Here, possibilities of defect engineering and surface modification of thin crystals are explored by Ar + dosing and vacuum annealing. Chlorine is easily removed from the surface, which reduces the Ru valence and eventually leaves a Ru rich surface layer behind. A peculiar thickness dependence of the work function emerges after Ar + sputtering, which is ascribed to the remaining chlorine concentration. This work elucidates material properties of thin α‐RuCl3 and introduces concepts of property engineering to create homojunctions and control level alignment by standard in situ methods. Abstract : Large work function modifications of thin exfoliated α‐RuCl3 flakes by argon sputtering are reported in this study. The value of the work function after treatment depends on the thickness of the flakes. From photoemission spectroscopy it is found that the chlorine concentration after sputtering strongly depends on the flake thickness as well.